2005
DOI: 10.1103/physrevlett.95.081103
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limits on Gravitational-Wave Emission in Association with the 27 Dec 2004 Giant Flare of SGR1806-20

Abstract: At the time when the giant flare of SGR1806-20 occurred, the AURIGA "bar" gravitational-wave (GW) detector was on the air with a noise performance close to stationary Gaussian. This allows us to set relevant upper limits, at a number of frequencies in the vicinities of 900 Hz, on the amplitude of the damped GW wave trains, which, according to current models, could have been emitted, due to the excitation of normal modes of the star associated with the peak in x-ray luminosity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The choice of the two long first periods is due to the special profile of the light curves, but it is also opportune to avoid any uncertainty about the time delay between the two emissions that make the time reference definition difficult in the correlation study. Nevertheless, relative to the GF, it is possible to restrict the measurement period because the impinging time of a light-speed signal onto the GW detectors is known [14]. Since the three different lengths (26s, 46s, 1s) do not allow us to employ an easy algorithm for a uniform analysis from the statistical and physical point of view, we divide the two long periods into a number of contiguous intervals, 1s for each one, obtaining a comprehensive sample of 73 independent segments for performing measurements.…”
Section: A On-source Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of the two long first periods is due to the special profile of the light curves, but it is also opportune to avoid any uncertainty about the time delay between the two emissions that make the time reference definition difficult in the correlation study. Nevertheless, relative to the GF, it is possible to restrict the measurement period because the impinging time of a light-speed signal onto the GW detectors is known [14]. Since the three different lengths (26s, 46s, 1s) do not allow us to employ an easy algorithm for a uniform analysis from the statistical and physical point of view, we divide the two long periods into a number of contiguous intervals, 1s for each one, obtaining a comprehensive sample of 73 independent segments for performing measurements.…”
Section: A On-source Regionmentioning
confidence: 99%
“…III A, the physical regions were chosen on two long sequences of 26s plus 46s , corresponding to the highest electromagnetic (EM) peaks of the October 5th outburst, and on 1s centered around the trigger time of the GF on December 27th. The long period, in the case of the outburst, and knowledge of the arrival time on Earth of a light-speed signal at the time of the GF [7,14] are circumstances particularly opportune to avoid uncertainty in the analysis focusing on the reference time of the gravitational radiation. The expected distribution under the null-hypothesis is built using real data, with random time shifts of one GW detector with respect to the other one (Sec.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strongest of the magnetar flares has been considered in the literature as potential multi-messenger gravitational wave sources, which has prompted targeted gravitational wave searches [84][85][86][87][88]. Presently, these searches have placed upper limits on gravitational wave energies of 1.4 × 10 49 erg for the f -mode (i.e.…”
Section: Magnetars and Gravitational Wavesmentioning
confidence: 99%
“…This corresponds to a characteristic isotropic energy release at the source of the order of 10 K8 solar masses for the 100 Hz frequency region, where the predicted QPO frequencies and LIGO's best sensitivity match. The previous search carried out with the Auriga detector (Baggio et al 2005) reported a limit of the order of 10 K6 solar masses for the 900 Hz frequency region where this detector is sensitive. Analyses of the LIGO data for more recent flares (SGR 1900C14 andSGR 1806-20) are being carried out.…”
Section: (A ) Current Situation With Interferometric Detectorsmentioning
confidence: 99%